2005
DOI: 10.1007/s00418-005-0106-9
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro model for studying vascular injury after laser microdissection

Abstract: We have developed an in vitro model for studying vascular injury. After 7-10 days in a three-dimensional collagen gel culture, capillary-like tubes were formed in the collagen gels. We injured these capillary-like tubes with a laser microdissection system or a scrape method with razors and then examined the collagen gel culture by phase contrast and electron microscopy. After laser injury, profuse necrotic cells were observed around the injured capillary-like tubes and within the tubular lumen compared to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Using a three-dimensional (3D) collagen gel culture, we have conducted electron microscopic studies [14, 15] and immunohistochemical studies of fibroblast growth factor- (FGF-) 2 and FGF-9 [16]. Additionally, we have used 3D collagen gel cultures to test angiogenic and anti-angiogenic agents (TNF- α and thalidomide) [17, 18] to study vascular injury after laser microdissection [19] and for profiling of DNA microarray gene expression during angiogenesis [20]. The 3D collagen gel culture system provides a simple and rapid method to analyze angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Using a three-dimensional (3D) collagen gel culture, we have conducted electron microscopic studies [14, 15] and immunohistochemical studies of fibroblast growth factor- (FGF-) 2 and FGF-9 [16]. Additionally, we have used 3D collagen gel cultures to test angiogenic and anti-angiogenic agents (TNF- α and thalidomide) [17, 18] to study vascular injury after laser microdissection [19] and for profiling of DNA microarray gene expression during angiogenesis [20]. The 3D collagen gel culture system provides a simple and rapid method to analyze angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…We applied the 3D collagen gel culture as an in vitro model of vascular injury [163]. After 7-10 days of culture, capillary tubes were observed in the collagen gels.…”
Section: Collagen Gel Culture As An In Vitro Model For Studying Vascumentioning
confidence: 99%
“…This study revealed that granulosa cells express stable amounts of inhibin-subunit mRNA independently of antral formation in immature rat ovaries. An interesting application of the LMD technique is to induce cell injury as reported in an in vitro model of vascular injury (Fujita et al 2006). Capillary-like tubes formed in culture were injured by a precisely focused laser pulse, making LMD an ideal tool for inducing and studying aspects of vascular injury.…”
Section: Methods and Hardware Developmentsmentioning
confidence: 99%